Vpliv prikritega oglaševanja na nakupno vedenje potrošnikov knjig - Rojec, Helena (Knjižnica, 2012)
Covert advertising is a form of illegal marketing when a text is published as editorial content although it is ordered and paid for by the advertiser. Covert advertising has an increasing influence on book consumption and on book consumers whose choices are often made unconsciously. They are frequently affected by various psychological factors such as motives, perceptions, attitudes and personality. The aim of the survey was to find out purchasing habits of book consumers, reasons for buying books and the amount of money they are willing to spend ob books. We were interested whether consumers know that covert advertising is illegal and that it influences their behaviour. A web questionnaire accessible for three months was completed by 470 respondents. The results show that most respondents like to purchase books. Most often they buy books that are classified as the light reading (novels, thrillers, etc.). When buying books they usually pay attention to the book genre, its title and author. The survey results also point to the poor understanding of the term "covert advertising". Thus, they could be an incentive to raise consumers awareness of this form of advertising. More stringent control of media editors and tougher penalties for offenders are suggested as well as a public list of all those who in any way contribute to misleading the public.
Keywords: knjigotrštvo; knjižni trgi; potrošniki; uporabniki; knjige; prikrito oglaševanje; nakupi